Changes Resulting from Paranormal/Spiritual Experiences and their Effects on People’s Wellbeing: An Exploratory Examination - Parra, Alejandro (Journal for the Study of Spirituality, 2014)
The aims of this study were to evaluate the effects of paranormal and mystical/spiritual experiences on people’s lives and to evaluate changes resulting from such experiences. Twenty-four participants attended workshops about paranormal/spiritual experiences. The Index of Changes Resulting From Experiences and a checklist of possible effects of paranormal or transcendent experiences were used. All of the respondents reported at least one paranormal experience, and 83% reported at least one transcendent experience. The high percentage of paranormal experiences reported may reflect the fact that respondents were recruited based on interest in parapsychology and the paranormal. Seventy per cent now have a purpose in life as a result of their paranormal or transcendent experience; 62% have had paranormal and/or transcendent experiences since childhood; 54% said they became significantly more spiritual or religious as a result of their experiences; and 54% were helped to understand and accept death. The fact that anomalous experiences apparently induce positive reactions in some people provides a strong impetus for further research. This line of research also has significant implications for understanding better not only those people who volunteer to participate in parapsychological experiments but also the results of those experiments.